Entrepreneurship Diversification, Skill Relatedness and Regional Economic Evolution - Frank Neffke; Martin Henning (European Regional Science Association (ERSA), 2010)
The literature in economic geography has recently shown a growing interest in the path dependent transformation of regional economies. According to evolutionary accounts, the development of regional economies can be regarded as a result of technological branching processes, where the development of the past conditions the future opportunity space of regions. In this paper, we provide a specific explanation as to why the present structure of regional economies conditions their future development. We maintain that regions are more likely to diversify into industries that are related to their existing production portfolio, than into industries that are not related. Within such a setting, entrepreneurship can be viewed as one of the main channels for regional diversification. We specifically investigate how relatedness structures and regional entrepreneurship processes interact to provide vital understanding about the mechanisms behind regional economic evolution. A novel method, "skill relatedness", is used to define which industries are more related than others. The method defines relatedness between industries in terms of the extent to which the industries depend on similar human capital. We establish the skill-relatedness among different industries by investigating labor flows. This allows us to conceptualize the entire economy, manufacturing as well as services, as a network of industries that are connected to one another in terms of similarities in the human capital they use. In the empirical investigations, we use Swedish employer linked data on all 4.7 million individuals on the Swedish labor market 2004-2007. Using the skill-relatedness information and distinguishing between local diversification due to entrepreneurial activity, due to the expansion of local firms, or due to the expansion of non-local firms, we find that the probability that a new industry enters a Swedish region in any of these ways is strongly dependent on whether the industry is skill-related to many of the region's core industries. Local economies are most likely to add industries to their portfolios that are skill-related to their industrial cores. The results suggest that skill relatedness is a fruitful tool to investigate not only the workings of regional path dependency, but also how existing skill bases are used by diversifying entrepreneurs.
Keywords: 330